Computational and Statistical Methods in Intelligent Systems - Silhavy, Radek; Silhavy, Petr.; Prokopova, Zdenka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents real-world problems and pioneering research in computational statistics, mathematical modeling, artificial intelligence and software engineering in the context of intelligent systems. It gathers the peer-reviewed proceedings of the 2nd Computational Methods in Systems and Software 2018 (CoMeSySo 2018), a conference that broke down traditional barriers by being held online. The goal of the event was to provide an international forum for discussing the latest high-quality research results. .
An Analytical Modeling for Leveraging Scalable Communication in IoT for Inter-Domain Routing -- Multi-Hybrid SMOTE Cost Sensitive Ensemble Approach for Software Defect Prediction -- Alternative Approach to Fisher's Exact Test with Application in Pedagogical Research -- Development of the Forecasting Component of the Decision Support System for the Regulation of Inter-regional Migration Processes -- Using Blockchain Technology to Improve N-version Software Dependability -- Enhancing Feature Selection with Density Cluster for Better Clustering -- Enhancing Concurrent ETL Task Schedule with Altruistic Strategy -- A Binary Percentile Sin-Cosine Optimisation Algorithm Applied to the Set Covering Problem -- Particular Analysis of Normality of Data in Applied Quantitative Research -- Towards Smartphone-based Navigation for Visually Impaired People.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence